Identifikasi Status Hara N Lahan Sawah pada Daerah Irigasi Kedunglimus Arca Kiri, Di Kecamatan Kembaran Kabupaten Banyumas - Agustine, Leony; Widiatmoko, Teguh; Begananda, Begananda (AGROSCRIPT: Journal of Applied Agricultural Sciences, 2020)
Paddy soil is land that is important in Indonesia as a major resource for growing rice in rice production. The main problems in rice cultivation in paddy fields is the transfer function, especially fertile and irrigated paddy fields into industrial areas and urban sprawl. The study aims to determine the amount of the nutrient content of N and determine the availability of nutrients N correlation with the production of rice in paddy fields in the area of the left arca of weir irrigation in Sub-District Kembaran Banyumas. The experiment was conducted in paddy fields in the area of the left arca of weir irrigation in Sub-District Kembaran Banyumas and followed with the analysis of the soil at the Laboratory Institute for Agricultural Technology in Yogyakarta and in the Laboratory of Soil Science, Faculty of Agriculture Unsoed. The experiment was conducted in March and May 2015. The study was conducted by survey method, in-depth review the level of accuracy (semi detail) with scale in map 1: 50,000. The determination of sample points is based on Homogeneous Soil Map Unit (SLH), which is made by overlay map on the map of soil types, slope maps and land use maps of research areas. The number of samples is 8, which is located on the 5 villages. The variables were observed and measured in the study include the main variables, namely N-total and N-available and include support variable-organic C content, soil pH, pH of water irrigation, CEC and interviews with farmers. The results showed that N-total content at all SLH is low, i.e. 0.166% in SLH A1f and 0.173% in SLH A2f . The content of N-available (N-NH4) in all SLH are 157 ppm in SLH A1f and 163 ppm in SLH A2f.